Identities and Foreign Policies in Russia, Ukraine and Belarus - White, Stephen. author. aut Link
X, 350 p.
Keywords: This book maps changing definitions of statehood in Russia, Ukraine and Belarus as a result of their exclusion from an expanding Europe. The authors examine the perceptions of the place of each state in the international political system and its foreign policy choices, and draw comparisons across the region.